Analisis dan Rekomendasi Upaya Penerapan Penggunaan QRIS Bagi Pedagang di Pasar Cikurubuk Tasikmalaya - Arya Budi Saputra; Adam Hermawan; Syti Sarah Maesaroh (Jurnal Transformasi Bisnis Digital, 2024)
The payment digitization process is inherent for MSMEs to improve they transaction. Digital payments that starting to be demand today is QR codes, namely QRIS. One of the cities that used QRIS is Tasikmalaya City. Cikurubuk Market is one of markets that has started to implement QRIS from 2020. However, until now the implementation are still not effective in use. This study to analyze and provide recommendations regarding efforts to implement QRIS in Cikurubuk Market, Tasikmalaya City, with an approach from the Technology Acceptance Model (TAM) theory. The results that perceived usefulness still does not have an impact and usefulness on the performance merchants because of the lack of buyers using QRIS and support systems that are still lacking. In perceived ease of use, merchants understand how to use QRIS because it is easy, even though the role of the organizers themselves still does not provide good socialization. From these two perceptions, of course, it forms the attitude and intention of the traders that they will continue to use QRIS in their shophouses. The biggest hope for the organizers is to carry out socialization and increase their seriousness to implement this QRIS so that it can be useful in practice.